Hybrid treatment of a tight aortic stenosis with critical calcified left main disease in a patient with poor left ventricular function - Kübler, Piotr; Onisk, Grzegorz; Rachwalik, Maciej; Przybylski, Roman; Reczuch, Krzysztof; Protasiewicz, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
We present a case of a 74-year old woman with a history of diabetes, hypertension, carotid endarterectomy and stenting of iliac arteries because of peripheral artery disease (PAD), admitted with the recognition of non ST-segment elevation myocardial infarction. Immediate coronary angiography revealed multivessel disease with critical calcified left main (LM) stenosis (Figure 1 A). Additionally, tight aortic stenosis (AS) with reduced left ventricle ejection fraction (LVEF 40%) was diagnosed. Unfortunately, after transfer to the intensive care unit pulmonary oedema occurred, successfully treated with pharmacotherapy. An urgent heart team meeting was held and the patient was disqualified from open-heart surgery because of comorbidities and high risk (EuroSCORE II – 17%). We decided to perform a hybrid procedure, including one stage balloon aortic valvuloplasty (BAV), percutaneous coronary intervention (PCI) and finally transcatheter aortic valve implantation (TAVI). Moreover, computed tomography revealed highly calcified aortic annulus and due to PAD only an alternative approach for TAVI was possible (Figure 1 B corner).